Habitat Suitability of Ziziphus spina‐christi and Ziziphus nummularia in a Changing Climate in the Khalijo‐Omanian Zone, Iran - Saeed Behzadi; Gholamabbas Ghanbarian; Rasool Khosravi; Roja Safaeian; Hamid Reza Pourghasemi (Ecology and Evolution)
ABSTRACT Climate change, a global threat of utmost significance, has the potential to trigger shifts in biodiversity distribution and the emergence of novel ecological communities. While considerable research has focused on predicting the impacts of climate change on the range shift of species, a critical yet often overlooked aspect is the role of changing climate on plants in hot, arid, and poorly known ecosystems. We employed an ensemble species distribution modeling framework to investigate how climate change might affect the spatial range of two significant indicator species, Ziziphus spina‐christi and Ziziphus nummularia, within the hot and arid Khalijo‐Omanian ecosystem of Iran. We ran the models for the current species distribution using climatic variables and then projected the models for two future periods (2041–2070 and 2071–2100) under different climate scenarios. These findings suggest that both species respond differently to climate change under different climatic scenarios. Some regions may undergo range expansion, whereas others may experience range contraction due to shifting environmental conditions. Overall, both species are projected to shift their range towards higher latitudes as climatic conditions evolve. Conservation and management measures, including the identification of priority areas, are crucial for protecting these species. The conclusions of this study are valuable to biodiversity conservation authorities, local stakeholders, and individuals dedicated to preserving Ziziphus habitats.